Indubitable Truth in Science? - Joarder, Siddhartha Shankar (Philosophy and Progress, 2012)
DOI: http://dx.doi.org/10.3329/pp.v50i1-2.11923 Philosophy and Progress: Vols. XLIX-L, January-June, July-December, 2011, p.65-88